Peran Home Industry Kue Khas Cangkiang Dalam Menngkatkan Pendapatan Keluarga Menurut Perspektif Ekonomi Islam Di Nagari Batu Taba Kecamatan Ampek Angkek - Mutiara Ramadhani Yasmin; H. Harfandi (BADAN PENERBIT STIEPARI PRESS, 2023)
The purpose of this article is to find out the role of the typical Cangkiang cake home industry in Nagari Batu Taba, Ampek Angkek District. The research method uses a qualitative approach, where research information is collected through observation, interviews and documentation. The data analysis technique used is an interactive technique. The steps taken are data reduction, data presentation and conclusion or verification. Based on the results of research conducted by the Cangkiang typical cake home industry, it can be stated that: 1) there is an increase in the income of the owner of the Cangkiang typical cake home industry. This can be seen from the increase in the income of home industry owners from before. Now, with the existence of a typical Cangkiang cake home industry, it can increase income to meet family needs and their children's education costs. In accordance with Islamic economic values, humans are encouraged to seek sustenance and God's grace so that their needs are met. 2) based on an Islamic economic review, that the home industry for typical Cangkiang cakes carried out by business owners in Nagari Batu Taba, Ampek Angkek District, is carried out properly and according to Islamic law, namely by increasing the income of business owners where Allah SWT has advised his people in QS. Al-Jumu'ah verse 10 to seek sustenance and achieve God's favor on earth.